2015
DOI: 10.5194/isprsarchives-xl-3-w2-31-2015
|View full text |Cite
|
Sign up to set email alerts
|

Feature Descriptor by Convolution and Pooling Autoencoders

Abstract: ABSTRACT:In this paper we present several descriptors for feature-based matching based on autoencoders, and we evaluate the performance of these descriptors. In a training phase, we learn autoencoders from image patches extracted in local windows surrounding key points determined by the Difference of Gaussian extractor. In the matching phase, we construct key point descriptors based on the learned autoencoders, and we use these descriptors as the basis for local keypoint descriptor matching. Three types of des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…It extends our previous descriptor learning work on Convolutional Neural Networks (CNN; Chen et al, 2015). As a CNN has a natural "deep" architecture, we expect this architecture to have a stronger modelling ability which can be used to produce invariance against more challenging transformations, which classical manually designed descriptors cannot cope with.…”
Section: Introductionmentioning
confidence: 74%
“…It extends our previous descriptor learning work on Convolutional Neural Networks (CNN; Chen et al, 2015). As a CNN has a natural "deep" architecture, we expect this architecture to have a stronger modelling ability which can be used to produce invariance against more challenging transformations, which classical manually designed descriptors cannot cope with.…”
Section: Introductionmentioning
confidence: 74%
“…Unsupervised learning methods such as autoencoders do not suffer from dependence on labelled data. Chen et al were the first to apply autoencoders to learn local image descriptors [19]. Their method shows promising results, however, the techniques they are using are today no longer modern (e.g.…”
Section: Related Work a Local Image Descriptorsmentioning
confidence: 99%
“…However, they have been less studied so far for learning local image descriptors. The work of Chen et al [19] reported an AEbased descriptors showing promising results, however, the methods they used are no longer considered state of the art. We proposed in our previous work an approach for learning local image descriptors based on convolutional autoencoders [20], [21] and variational autoencoders [22].…”
Section: Introductionmentioning
confidence: 99%
“…The application of autoencoders to the problem of descriptor learning was first proposed by Chen et al [18]. In our previous work [19], [20], we proposed autoencoder-based patch descriptors designed for applications with many patch comparisons within a single image.…”
Section: Related Workmentioning
confidence: 99%